2001
DOI: 10.1016/s0550-3213(01)00137-7
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating photons with gravitational radiation

Abstract: The nature of superluminal photon propagation in the gravitational field describing radiation from a time-dependent, isolated source (the Bondi-Sachs metric) is considered in an effective theory which includes interactions which violate the strong equivalence principle. Such interactions are, for example, generated by vacuum polarisation in conventional QED in curved spacetime. The relation of the resulting light-cone modifications to the Peeling Theorem for the Bondi-Sachs spacetime is explained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…Many examples of the Drummond-Hathrell effect in a variety of gravitational wave, black hole and cosmological spacetimes have been studied [11,38,39,15] etc. The black hole cases are particularly interesting, and it is found that for photons propagating orbitally, the light cone is generically modified and superluminal propagation occurs.…”
Section: A Time Machine From Superluminal Photons In Gravitational Fimentioning
confidence: 99%
See 2 more Smart Citations
“…Many examples of the Drummond-Hathrell effect in a variety of gravitational wave, black hole and cosmological spacetimes have been studied [11,38,39,15] etc. The black hole cases are particularly interesting, and it is found that for photons propagating orbitally, the light cone is generically modified and superluminal propagation occurs.…”
Section: A Time Machine From Superluminal Photons In Gravitational Fimentioning
confidence: 99%
“…Outgoing radial null geodesics are associated with ℓ µ while incoming null geodesics have tangent vector n µ in the obvious Newman-Penrose basis [41,15]. The metric functions have asymptotic expansions near I + for large luminosity distance r. We just need those for the functions γ ± δ, which correspond to the two independent gravitational wave polarisations:…”
Section: A Time Machine From Superluminal Photons In Gravitational Fimentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Einstein's equivalence principle (EEP), which locally encompasses both the principles mentioned above, can be understood as the requirement that spacetime is Riemannian and, as a consequence, has at each point a local inertial frame [1]. Accordingly, the EEP is a statement about purely local effects.…”
Section: Introductionmentioning
confidence: 99%
“…The Newman-Penrose (NP) formalism has been found to be an elegant way of analyzing the results in the SEP violating cases. Quantum gravitational optics attributes velocity shift and null cone modification at each point to only a single NP scalar for each of the Ricci and Weyl tensors, namely Φ 00 and Ψ 0 respectively [6]. The question is what would be the role of other NP scalars in determining the forms of Ricci and Weyl tensors?…”
Section: Introductionmentioning
confidence: 99%